2018
DOI: 10.3934/microbiol.2018.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Broiler chicken carcasses and their associated abattoirs as a source of enterotoxigenic <em>Clostridium perfringens</em>: Prevalence and critical steps for contamination

Abstract: Clostridium perfringens ranks among the three most frequent bacterial pathogens causing human foodborne diseases in Canada, and poultry meat products are identified as a source of infection for humans. The objective of the current study was to estimate the proportion of broiler chicken flocks, carcasses and various environmental samples from critical locations of the slaughter plant positive for the presence of C. perfringens enterotoxin encoding gene ( cpe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The frequency of cpe + C. perfringens type A recovered from chicken carcasses in the current study coincided with the findings of Gaucher et al . (2018) and Hu et al . (2018) which indicated a higher contamination from the intestinal contents during slaughtering processes or through contact with contaminated surfaces in slaughterhouses (Rouger et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The frequency of cpe + C. perfringens type A recovered from chicken carcasses in the current study coincided with the findings of Gaucher et al . (2018) and Hu et al . (2018) which indicated a higher contamination from the intestinal contents during slaughtering processes or through contact with contaminated surfaces in slaughterhouses (Rouger et al .…”
Section: Discussionmentioning
confidence: 96%
“…2017), broiler chicken carcasses (Guran and Oksuztepe 2013, Gaucher et al . 2018; Hu et al . 2018) and diarrhoeic human cases (Yadav et al .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sampling. Environmental (E) samplings were carried out at seven critical sampling locations (CSLs) (23). CSLs were defined as follows: E1, the feather-plucking rubber fingers; E2, the conveyor belt between the live-receiving and the evisceration departments; E3, the eviscerating machine; E4, the floor surface in the evisceration department; E5, the conveyor belt before chilling; E6, the conveyor belt after chilling; and E7, a stainless steel equipment surface in contact with the meat product and located in the cut-up room (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of genomic DNA. A DNA extraction protocol using a 10% Chelex 100 (Bio-Rad Laboratories, Mississauga, Ontario, Canada) solution in water was applied (23). In brief, three to five colonies of each pure Salmonella isolate grown on blood agar plates were suspended in 1 mL of sterile water, vortexed, and centrifuged at 12,000 3 g for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies indicated that chicken products have high contamination rates of C. perfringens in the retail market (Miki et al, 2008;Wen & Mcclane, 2004), which may be caused by improper storage in the retail market, or the contamination from the environment in retail stores. At the same time, it has been reported that unreasonable treatment (such as slaughterhouses are not disinfected in time or slaughtering operations are not standardized) in the slaughtering process may also cause cross contamination of C. perfringens in meat products (Álvarez-Pérez et al, 2018;Gaucher et al, 2018;Li et al, 2019). Modern poultry slaughtering relies on highly automated processes and equipments, and preventing chicken carcasses from bacterial contamination is a constant challenge for processors who must comply with regulatory guidelines (Alzubeidi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%